Drug Dosing in Obesity Volume I: Antimicrobials - Zaidi, Syed Tabish R.; Roberts, Jason A. (Springer International Publishing : Imprint: Springer, 2016)
This book provides an up to date review on antimicrobials dosing in obese patients, including practice recommendations for clinical use. The book is written by a group of doctors and pharmacists working in infectious diseases practice and research. The introductory chapter outlines the important physiological changes in obesity including factors affecting the dosing of antimicrobials in obese patients. The introductory chapter is followed by ten chapters covering the major classes of antibiotics, antifungals, and antivirals. Each chapter briefly discuss the pharmacokinetics changes related to obesity and a summary of the relevant up-to-date literature. Specific dosing recommendations are provided for each class supplemented by real-life examples as clinical cases that are included as an appendix to the book. The book is a useful resource for clinicians, students and researchers needing up-to-date information on antimicrobial dosing in obese patients. Doctors, pharmacists, nurses working in hospital settings, and students of health courses (medical, pharmacy and nursing students) will find this book particularly useful.